Thermal Surface Texture EHL Analysis of Water- lubricated Tenmat Bearing - Dong Ning; Wang Youqiang; Liu Qian; Huang Xingbao (Jixie chuandong)
The elastohydrodynamic lubrication geometric model of surface texture bearing is set up. The numerical simulation of elastohydrodynamic lubrication property of water- lubricated tenmat bearing with circular dimple,rectangular dimple and triangular- rectangular dimple is carried out. The results show that,considering the bearing surface texture makes pressure and film thickness oscillating,the pressure peak and the minimum film thickness decreased. The minimum film thickness is decreased with the increase of slip,the minimum film thickness of circular dimple texture is larger than the rectangular dimple,far larger than the triangular-rectangular dimple. With the increase of the dimple depth,the oscillating of pressure is not obvious,the oscillating of film thickness increased,the minimum film thickness decreased. The bearing with triangular- rectangular is detrimental for lubrication.